2007
DOI: 10.1111/j.1467-6486.2007.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Managers' Exploration and Exploitation Activities: The Influence of Top‐Down, Bottom‐Up, and Horizontal Knowledge Inflows*

Abstract: This paper develops and tests hypotheses on the influence of a manager's knowledge inflows on this manager's exploration and exploitation activities. Based on a survey among managers of a leading electronics firm, the findings indicate, as expected, that top-down knowledge inflows of a manager positively relate to the extent to which this manager conducts exploitation activities, while they do not relate to a manager's exploration activities. Furthermore, as expected, bottomup and horizontal knowledge inflows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
572
1
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 535 publications
(602 citation statements)
references
References 93 publications
17
572
1
12
Order By: Relevance
“…In leading suitable responses to these challenges, it has been found that middle managers may crossleverage capabilities by "moving" existing capabilities to areas where they believe these capabilities can generate value (Taylor & Helfat, 2009). It has also been established that top-down knowledge inflows to middle managers tend to foster exploitation, and horizontal and bottom up knowledge inflows more likely lead to exploration (Mom et al, 2007).…”
Section: Mnc Knowledge Flows At the Individual-level: The Central Rolmentioning
confidence: 99%
See 1 more Smart Citation
“…In leading suitable responses to these challenges, it has been found that middle managers may crossleverage capabilities by "moving" existing capabilities to areas where they believe these capabilities can generate value (Taylor & Helfat, 2009). It has also been established that top-down knowledge inflows to middle managers tend to foster exploitation, and horizontal and bottom up knowledge inflows more likely lead to exploration (Mom et al, 2007).…”
Section: Mnc Knowledge Flows At the Individual-level: The Central Rolmentioning
confidence: 99%
“…While front-line staff might possess and require knowledge that is very specific to their immediate task environment, and top management provides strategic direction and knowledge with regards to the general product-market, technological or geographical domain (Mom, Van Den Bosch, & Volberda, 2007), middle managers operate at the nexus where this specific, bottom up knowledge and general, top-down knowledge collide. Interacting across these vertical interfaces offers subsidiary managers channels to mobilize knowledge from subsidiary front-line and higher-level management both, located at the focal subsidiary and other international sites.…”
Section: Mnc Knowledge Flows At the Individual-level: The Central Rolmentioning
confidence: 99%
“…The role of managers in resolving tensions related to such opposing and incompatible organizational goals is critical (Mom, Van Den Bosch, & Volberda, 2007;Yoon & Chae, 2012). In order for managers to consistently meet task objectives, they need to assume multiple roles, effectively tackle contradictory tasks and achieve short and a long term goals that stem from their job description (Smith & Tushman, 2005).…”
Section: The Effects Of Hard and Soft Influence Tactics On Performancementioning
confidence: 99%
“…But we are interested in Mom, Van Den Bosch, and Volberda (2007) because they relate exploitation and exploration strategies to mechanisms of coordination and decision making, it fits our study best. For these reasons, we chose and adapted six items from Mom et al (2007) to measure exploitation strategy and five items to measure exploration strategy.…”
Section: Exploitation and Exploration Strategiesmentioning
confidence: 99%